(untitled) (Stavební obzor - Civil Engineering Journal, 2017)
The paper presents behaviour of gusset plate connections in compression. The finite element method is employed to examine the buckling resistance of the gusset plate connections. The FE model is validated to results of physical tests and verified by an analytical solution based on existing formulas. Finally, a parametric study is performed. The studied parameters include gusset plate thickness and size, types of connection between the gusset plate and frame members and stiffeners.